Implementasi Metode First Come First Served Dalam Sistem Informasi Rental Mobil - Ilham Indra Saputra; Ucuk Darusalam (STMIK Budi Darma, 2022)
Car rental is a transportation service that offers rental services for vehicles. This business can also help the community or immigrants who need four-wheeled vehicle rental services for various purposes and needs. Car rental currently still uses the bookkeeping method and manually analyzes the data for recording the rental transaction data. Website-based information systems also have an important role in supporting progress in the application of the car rental business so that they can carry out car rental business activities optimally with progress. Website-Based Car Rental Information System is designed using Sublime tools, Notepad++ and uses a MySQL database. The system design method used is First Come First Served, which is a system that is used to make reservations by paying in advance. The method applies a system of advance payment in advance to get this car unit for rent. From this research, the First Come First Served method is very beneficial for the admin because if there is no rental status payment, it will be taken by other users with the desired car unit.